Laser induced phenomena in γ-glycine crystals - Wojciechowski, Artur; Alzayed, Naser; Kityk, Ivan; Berdowski, Janusz; Tylczyński, Zbigniew (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The photoinduced changes of absorption within the spectral range 200–800 nm and optical second harmonic generation caused by illumination by the cw second harmonic generation of the Nd:YAG laser (λ = 532 nm) and power about 400 mW were investigated. We have established that increasing the time of illumination by the second harmonic generation of the Nd:YAG laser leads to the occurrence of one strong spectral minimum at 319 nm and another less strong at 420 nm. Increasing the time of illumination leads to a slight red spectral shift of the photoinduced minima. The absence of a substantial increase in temperature indicates that the principal role is played here by the photooccupation of the trapping levels. The effect is observed in a wide spectral range of the incident photoinduced angles, however, the beam should possess a good Gaussian-like form and to be space homogenous. The results were reproduced with precision up to 3–4% which was achieved due to additional stabilization of the photoinduced laser power by double control of the power.
Optica Applicata, Vol. 40, 2010, nr 4, s. 1007-1012
Keywords: optyka; optical absorption; organic crystals